Pengaruh Pendidikan Ekonomi Keluarga, Literasi Ekonomi, Gaya Hidup Terhadap Perilaku Konsumtif Mahasiswa - Sugiarto, Apprillia Anggraeni; Amri, Fahimul (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2024)
The focus of this research is the influence of economic education in the family, economic literacy, and student lifestyle on student consumptive behaviour. The research uses a quantitative approach. The subject of this study is higher school students. Data analysis technique using path analysis. The population is 1,204 students, and the research sample is 300 students by determining proportional random sampling. The study results show that family economic education and economic literacy influence consumptive behaviour variables. Family economic education and consumptive behaviour affect lifestyle. Economic literacy has no significant effect but has a positive value on lifestyle. Family economic education influences consumptive behaviour toward lifestyle. Economic literacy influences consumptive behaviour toward lifestyle